2011
DOI: 10.1021/jf200295c
|View full text |Cite
|
Sign up to set email alerts
|

Galloylated Polyphenols as Inhibitors of Hemoglobin-Catalyzed Lipid Oxidation in Fish Muscle

Abstract: The influence of galloyl residues on the antioxidant mechanism of polyphenols to prevent hemoglobin-promoted lipid oxidation was investigated by using polyphenolic fractions with different degrees of galloylation: nongalloylated structures from pine bark (IVP), medium-galloylated from grape pomace (IVG), and high-galloylated from witch hazel bark (IVH). Hemoglobin (Hb) from the pelagic fish horse mackerel (Trachurus trachurus) was employed as a Hb standard. In vitro experiments showed an important increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Therefore, part of the astaxanthin and tocopherol would be recovered and remain active, thus more effectively inhibiting the formation of peroxides and at the same time protecting the content of polyunsaturated fatty acids. [48,50,51].…”
Section: Protective Effect Of Astaxanthin In Cooked Salmon Pastementioning
confidence: 99%
“…Therefore, part of the astaxanthin and tocopherol would be recovered and remain active, thus more effectively inhibiting the formation of peroxides and at the same time protecting the content of polyunsaturated fatty acids. [48,50,51].…”
Section: Protective Effect Of Astaxanthin In Cooked Salmon Pastementioning
confidence: 99%
“…To control Hb oxidation and Hb-induced lipid oxidation, the antioxidants including polyphenols and ascorbic acid are adopted because of their strong antioxidant properties. , As a member of poly-phenolic compounds in plants, flavonoids have received increasing attention in human diet. Numerous reports have indicated that free radical scavenging and metal chelating are usually considered as the important mechanisms responsible for the antioxidant properties of flavonoids . In a previous study, it has been demonstrated that gallic acid could act as a reductant to dose-dependently retard Hb oxidation by reducing met-Hb formation .…”
Section: Introductionmentioning
confidence: 99%
“…Pro-oxidants present in muscle tissue and the parts of viscera remaining after gibbing, which were washed out by the melting ice might be other factors affecting the oxidation potential of the compared fish species. In this case myoglobin might be the main pro-oxidant (Undeland et al 2004, Neira et al 2011. It plays an important role in oxidation of muscle lipids, especially in the presence of peroxides and hydroperoxides, in which case it can be converted to ferryl myoglobin, thus being the main source of haematin and free ion iron.…”
Section: Discussionmentioning
confidence: 99%